EFFECTIVENESS OF ONLINE LICENSING SERVICES ON MSME DEVELOPMENT: A CASE STUDY OF DPMPTSP SIDOARJO REGENCY - Ferdiansah , Lefan Afitra; Rustianingsih, Eni (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the effectiveness of online licensing services through the Online Single Submission (OSS) system in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Sidoarjo Regency. Method: A qualitative method with a case study approach was applied, involving MSME actors and DPMPTSP officers through interviews, observations, and document collection. Results:  The findings indicate that OSS simplifies the licensing process, enhances transparency, and accelerates the issuance of Business Identification Numbers (NIB). However, the main challenges identified include low levels of digital literacy and insufficient technical support, particularly for micro-enterprises in rural areas. The analysis employs Budiani’s effectiveness theory and Richard M. Steers’ concept of organizational effectiveness, which emphasizes that an organization’s success can be assessed by the extent to which individual behavior and institutional structures work in harmony to achieve predetermined goals. The results show that the indicators of socialization and monitoring function relatively well, while target accuracy and clarity of objectives still need improvement. Novelty: This study suggests enhancing digital literacy, simplifying the system, and providing continuous assistance to ensure that OSS becomes more inclusive and responsive to the needs of MSMEs in the region.